Measurement the Impact of Logisitc Management System on Economic Growth in Selected Asian Countries - Akhunzada, Taimoor Khan; Ali, Sher (Pakistan Journal of Humanities and Social Sciences, 2023)
This study intended to investigate the impact of on logistics management system on economic growth in selected Asian countries for the period of 2009-2018. Moreover, the impact of renewable energy consumption is association with logistics management system is also examined. There are six (06) sub-regions in Asia and from each region, two countries are selected. Effective logistic Management System is measured by different six (06) components are chosen to get the clear impact on growth. Hausman test suggested to use Random effect regression analyses for the said investigation. The results of the mentioned techniques showed that the impact of Logistics management system components i.e. LPIEA, LPIEC and LPIFS are found significant in the absence of renewable energy and CO2 was found effective to affect growth. While in the presence of renewable energy consumption the components of Logistics management system i.e. LPIAT, LPICQ, LPIEC and LPIQT are found significant to affect growth in the study area. Moreover, renewable energy consumption is found significant to affect growth. Policymakers in Asian countries should prioritize investment in these areas to promote sustainable development and contribute to global efforts to combat climate change.